Provisioning backhaul traffic flows in TDMA/OFDMA infrastructure Wireless Mesh Networks with near-perfect QoS - Szymanski, T H (2010 IEEE Sarnoff Symposium, 2010)
Scheduling and channel assignment algorithms to provision longer-term backhaul traffic flows in infrastructure TDMA/OFDMA Wireless Mesh Networks (WMNs) with near-perfect QoS are described. A recursive fair stochastic matrix decomposition algorithm is used to compute transmission schedules for all provisioned backhaul traffic flows between BSs. Each schedule consists of a sequence of permutations which specify active edges, which provide near-minimal delay and jitter and near-perfect QoS guarantees on a per-flow basis. A constrained graph coloring algorithm is used to color the permutations, to remove primary conflicts and minimize secondary conflicts. The colored edges are assigned to time-slots and are used to compute the antenna beamforming vectors and transmission power levels. The beamforming can use either a zero-forcing or an iterative MMSE algorithm. Each wireless link achieves a prescribed transmission rate and SINR such that the total transmission power in the WMN is minimized, subject to the per-flow QoS constraints. Extensive simulations of an essentially-saturated hexagonal TDMA/OFDMA WMN supporting backhaul traffic flows are reported.